In search of academic quality - Paradeise, Catherine 1946-; Thoenig, Jean-Claude 1940- (Palgrave Macmillan, 2015)
"Are higher education and research in the process of becoming more and more alike? Global standards such as performance rankings and New Public Management approaches provide an identical rationale for launching major reforms. The way to produce an academic quality at the local level is expected to be aligned according to such standards.In Search of Academic Quality questions the relevance of such an evolution scenario. Based on an international comparison observing in-depth a series of universities, the book suggests that diversity remains massive when considering how single institutions position themselves in terms of quality standards and combine resources, as well as the alternatives they have access to given their organizational and cultural governance path dependence. This volume explores a series of analytical tools applicable for management purposes such as improving academic quality upgrading. "..